Improving The Implementation Of The Profile Of Pancasila Student Strengthening Projects With Example - Ari Murniasih; Rahmat Mulyono (Risalah, Jurnal Pendidikan dan Studi Islam, 2023)
The influence of the school principal's example in improving the implementation of the Pancasila Student Profile Strengthening Project through increasing teacher self-confidence in the ABA Karangmojo XX Kindergarten Mobilization School, increasing the ability of teachers to prepare and carry out the process of the Pancasila Student Professional Strengthening Project and increasing teacher motivation to learn and increasing professional skills in run errands. The Principal of ABA Karangmojo XX Kindergarten Activator School is improving the implementation of the Pancasila Student Profile Strengthening Project by exemplary to open opportunities for the creation of complementary two-way communication. This approach is transformed into operational steps in the form of concrete steps. According to Ki Hajar Dewantara's educational concept, the among system consists of three things, namely "Ing ngarsa sung tuladha, Ing madya mangun karsa, Tut wuri handayani". The role of the Principal in terms of forming a Profile Project team and participating in planning a profile project, accompanying the course of the profile project and managing educational unit resources in a transparent and accountable manner, building communication for collaboration between parents of students, members of the education unit, and resource persons, conducting coaching periodically, plan, implement, reflect, and evaluate and learner-centered assessments. This operational step has proven to be able to increase teacher competence, especially in the implementation of the Pancasila Student Profile Strengthening Project.